THE EFFECT OF CHROMIUM STRESS ON MICRO-ANATOMICAL PROFILE OF CHILI (Capsicum annuum L.) - Nur Fitrianto; Siti Samiyarsih; Dede Winda Nur Fauziah; Sri Lestari (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Chromium contamination can affect morphological, physiological, and anatomical changes, especially in chili vegetative organs. This research aims to understand micro-anatomical structure of the vegetative organs of chili subjected to chromium stress. The aim of the research is to know whether there is a micro-anatomical character difference between contaminated and uncontaminated chromium. The experimental methods using a completely randomized design (CRD). The independent variable is five levels of chromium concentration, i.e., 0; 50; 100; 200; and 300 ppm. The method of preparing anatomical preparations of the stem using a non-embedding and embedding method. The parameters observed in root and stem are organ diameter, xylem, thick of epidermis, and cortex. In contrast, leaf organ parameter includes thick cuticle, epidermis, mesophyll, stomata size (length and width), and stomatal number. The research results showed that organ anatomical structure, i.e., root, stem, and leaf in chromium stress condition did not change. Chromium deposition causes a decrease in root diameter, xylem, thick cortex roots, stem diameter, xylem, the thickness of the epidermis and cortex, leaf epidermal thickness, mesophyll, size of stomata width and number. In contrast, the chromium stress causes an increase in the thickness of the root epidermis (43,18%), cuticle thickness (36,36%), and leaf stomata length (33,33%) of chili as chromium concentrations increase. The anatomical structure of chili leaves changes after being contaminated chromium stress.